Theoretical Modeling and Experimental Detection of the Extracellular Phasic Impedance Modulation in Rabbit Hearts - Iravanian, Shahriar; Herndon, Conner; Langberg, Jonathan J.; Fenton, Flavio H. (Frontiers in Physiology, 2019)
Theoretical cardiac electrophysiology focuses on the dynamic of the membrane and sarcoplasmic reticulum ion currents; however, passive (e.g., membrane capacitance) and quasi-active (response to small signals) properties of the cardiac sarcolemma, which are quantified by impedance, are also important in determining the behavior of cardiac tissue. Theoretically, impedance varies in the different phases of a cardiac cycle. Our goal in this study was to numerically predict and experimentally confirm these phasic changes. We calculated the expected impedance signal using analytic methods (for generic ionic models) and numerical computation (for the Beeler-Reuter ventricular model). Cardiac impedance is phase dependent with a sharp and transient drop at the onset of action potentials, followed by an increase during the plateau phase, and eventually a return to baseline in phase 3 of action potentials. This dip and dome pattern was confirmed in an ex-vivo rabbit heart model by the help of high-frequency sampling through a monophasic action potential electrode. The hearts were immobilized using a myosin-inhibitor to minimize motion artifacts. We observed phasic impedance changes in three out of four hearts with a dome amplitude of $2-6\,Ω$. Additionally, analytic works predict that the membrane impedance is frequency-dependent and exhibits resonance. This prediction was also confirmed by experiment. Measurement of phasic impedance modulation using an extracellular electrode is feasible and provides a non-invasive way to gain insight into the state of cardiac cells and membrane ionic channels. The observed impedance recordings are consistent with the dip and dome pattern predicted analytically.